Parameter Optimization of Segmental Multicluster Fractured Horizontal Wells in Extremely Rich Gas Condensate Shale Reservoirs - Zhipeng, Wei; Jinwei, Wang; Rumin, Liu; Tao, Wang; Guannan, Han (Frontiers in Earth Science, 2021)
For economic and efficient development of extremely high-condensate shale gas reservoirs, a numerical model of segmental multicluster fractured horizontal well was established considering the effect of condensate and desorption, and the optimization of fracturing segments, fracturing clusters, half-length of main fracture, fracture permeability, fracture mesh density, and fracture distribution patterns were studied. It is indicated that the horizontal well whose design length is 2,700 m performs best when it has 43 fracturing segments with three clusters in each segment and the fracture permeability is 300 mD. The production capacity of horizontal wells is positively linearly correlated with the half-length of fractures. Increasing fracture half-length would be an effective way to produce condensate oil near wellbore. An effective fractured area can be constructed to remarkably improve productivity when the half-length of the fracture is 50 m and the number of secondary fractures is four in each segment. On the basis of reasonable fracture parameters, the staggered type distribution pattern is beneficial to the efficient development of shale gas-condensate reservoirs because of its large reconstruction volume, far pressure wave, small fracture interference, and small precipitation range of condensate.